“Things Fall Apart?” Prospects of Solidarity in a Precarious World - Matthew Mabefam; Kennedy Mbeva; Issah Wumbla (Social Inclusion)
In this article, we examine the potential of solidarity to address global challenges in an increasingly precarious world. Solidarity involves individuals or groups supporting causes—whether ideas, people, or contexts—to combat marginalisation and injustice, even as such efforts frequently encounter resistance. This prompts the critical questions: What motivates solidarity, how is it expressed, and how effective is it in resolving the issues it seeks to address? Drawing on illustrative examples from a variety of social movements worldwide, we analyse the diverse forms of solidarity and the tensions that arise when dissent and resistance intersect with collective action. Despite these challenges, we argue that solidarity remains a viable framework for addressing some of today’s most pressing and complex issues. By exploring both the opportunities and obstacles it presents, we highlight solidarity’s enduring relevance and transformative potential in fostering meaningful change.